PEMBERDAYAAN MASYARAKAT DI DESA TERTINGGAL MELALUI EDUKASI PENGENDALIAN TEKANAN DARAH DENGAN CERDIK DALAM ASUHAN KEPERAWATAN KOMUNITAS - Lalu Amri Yasir Amri; Harlina Putri Rusiana; Zulkahfi; Putri Nindy Pariha; Rias Pratiwi Safitri; Ilham; Dewik Damayanti; Ni Made Sari Darmayanti; David Pratama Hakim; Della Septia Alfianti (Jurnal LENTERA, 2026)
Hypertension is a non-communicable disease with an increasing prevalence and remains a major public health problem, particularly in underdeveloped rural areas with limited access to health services. Low community knowledge regarding risk factors and hypertension control contributes to the high incidence of the disease. This community service activity aimed to improve community knowledge on blood pressure control through CERDIK-based health education within community nursing care. The activity was conducted through health education using lectures, interactive discussions, and leaflet media, preceded by a pretest and followed by a posttest to evaluate knowledge levels. The target participants were adults and elderly people living in an underdeveloped village in Central Lombok Regency. The results showed an improvement in community knowledge after the educational intervention. This activity indicates that community empowerment through CERDIK-based education can serve as an effective promotive and preventive strategy for hypertension control in underdeveloped rural areas.